Isolation, characterization, and genomic analysis of a novel bacteriophage MA9V-1 infecting Chryseobacterium indologenes: a pathogen of Panax notoginseng root rot - Zou, He; Ding, Yafang; Shang, Junjie; Ma, Chunlan; Li, Jinhua; Yang, Ye; Cui, Xiuming; Zhang, Jinhao; Ji, Guanghai; Wei, Yunlin (Frontiers in Microbiology, 2023)
Chryseobacterium indologenes is one of the primary causative agents of root-rot of Panax notoginseng, which significantly affected plant growth and caused economic losses. With the increasing incidence of antibiotic-resistant bacterial phytopathogens, phage therapy has been garnered renewed attention in treating pathogenic bacteria. However, the therapeutic potential of phage therapy on root-rot of P. notoginseng has not been evaluated. To address this gap, we isolated a novel lytic phage MA9V-1 infecting C. indologenes MA9 from sewage, and monitored the formation of clear and round plaques with a diameter of approximately 0.5-1.5 mm. Phage MA9V-1 exhibited rapid absorption (>75% in 8 min), a latency period of 20 min, and a burst size of 10 particles per cell. Transmission electron microscopy indicated that the phage MA9V-1 is a new myovirus hosting C. indologenes MA9. Sequencing of phage genomes revealed that phage MA9V-1 contained a linear double-stranded DNA genome of 213,507 bp with 263 predicted open reading frames, including phage structure, host lysing, and DNA polymerase/helicase, but no genes of tRNA, virulence and antibiotic resistance. Our proteomic tree and genomic analysis revealed that phage MA9V-1 share identity with Sphingomonas phage PAU and Tenacibaculum phage PTm1; however, they also showed apparent differences. Further systemic evaluation using phage therapy experiments on P. notoginseng suggested that phage MA9V-1 can be a potential candidate for effectively controlling C. indologenes MA9 infection. Thus, we have presented a novel approach to solving root rot in P. notoginseng.